Discrimination of genetic and geographical groups of grape varieties (Vitis vinifera L.) based on their volatile organic compounds - Šikuten, Iva; Štambuk, Petra; Tomaz, Ivana; Marchal, Cecile; Kontić, Jasminka Karoglan; Lacombe, Thierry; Maletić, Edi; Preiner, Darko (Frontiers in Plant Science, 2022)
Grape organic volatile compounds (VOCs) have important role in winemaking industry due to their contribution to wine sensory characteristics. Another important aspect are grapevine varieties used in specific regions or countries for wine production. Due to high variability of grapevine germplasm, it was classified based on their genetic and geographical origin into genetic-geographic groups (GEN-GEO). The aim of this research was to investigate VOCs in 50 red grapevine varieties belonging to different GEN-GEO groups. Study included varieties from groups C2 (Italy and France), C7 (Croatia), and C8 (Spain and Portugal). Analyzed VOCs belonged to aldehydes, ketones, acids, alcohols, monoterpenes, sesquiterpenes. The most abundant VOCs were aldehydes and alcohols, while the most numerous were sesquiterpenes. Using discriminant analysis, the GEN-GEO groups were clearly separated based on their volatile profile. C2 group was characterized by higher content of aldehydes and alcohols, C8 group was characterized by higher content of sesquiterpenes and acids. Group C7 was characterized by low amount of all classes of VOCs.